The property in Cajamarca houses (Peru) - Scaletti Cárdenas, Adriana (2012)
Domestic civil architecture is a very little studied subject in the intermediate cities of Peru, but it is, both in them as in thecapital, the most important and revealing part of the urban fabric and therefore of the city. This paper seeks to introduce thereader to the situation of the houses of Cajamarca (Peru), mainly those of the XVIII - XIX centuries, at the time of thefirst mining boom of Cajamarca with the exploitation of the silver veins of the neighboring Hualgayoc. As a result of thisboom, Cajamarca architecture and the interest of its inhabitants about personal luxury property developed at a significantlevel, as it is still possible to see through the filed records. The same documents show a city that despite being very little studiedin comparison with larger ones of the viceroyalty, has much to tell about a surprisingly rich and complex past.